2020
DOI: 10.1186/s12938-020-00824-w
|View full text |Cite
|
Sign up to set email alerts
|

Why brain-controlled neuroprosthetics matter: mechanisms underlying electrical stimulation of muscles and nerves in rehabilitation

Abstract: Delivering short trains of electric pulses to the muscles and nerves can elicit action potentials resulting in muscle contractions. When the stimulations are sequenced to generate functional movements, such as grasping or walking, the application is referred to as functional electrical stimulation (FES). Implications of the motor and sensory recruitment of muscles using FES go beyond simple contraction of muscles. Evidence suggests that FES can induce short- and long-term neurophysiological changes in the cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 153 publications
(344 reference statements)
3
43
0
1
Order By: Relevance
“…On the other hand, many previous studies reporting therapeutic effect of continuous cervical tSCS on upper-limb motor function have delivered stimulation combined with functional task performance [16][17][18]26]. Voluntary engagement combined with afferent recruitment may elicit a form of Hebbian plasticity in the CNS during application of electrical stimulation [48,49]. A recent study reported that continuous cervical tSCS combined with hand training enhanced hand motor outputs, increased F-wave amplitudes and persistency, reduced TMS-induced resting motor thresholds, and facilitated MEP amplitudes after the intervention [19].…”
Section: Voluntary Involvement Combined With Continuous Cervical Tscs May Be Required For Effective Neuromodulationmentioning
confidence: 99%
“…On the other hand, many previous studies reporting therapeutic effect of continuous cervical tSCS on upper-limb motor function have delivered stimulation combined with functional task performance [16][17][18]26]. Voluntary engagement combined with afferent recruitment may elicit a form of Hebbian plasticity in the CNS during application of electrical stimulation [48,49]. A recent study reported that continuous cervical tSCS combined with hand training enhanced hand motor outputs, increased F-wave amplitudes and persistency, reduced TMS-induced resting motor thresholds, and facilitated MEP amplitudes after the intervention [19].…”
Section: Voluntary Involvement Combined With Continuous Cervical Tscs May Be Required For Effective Neuromodulationmentioning
confidence: 99%
“…Besides social stigma, discrimination, and a high prevalence of severe depression in people living with epilepsy, a recent productivity study in Australia indicated that just a 5% improvement in seizure control could result in more than AU$2 billion in economic benefit for the country [62]. One way of increasing seizure control or increasing the quality of life for patients living with epilepsy is to provide a reliable and personalized way to predict seizures or detect them early to intervene using neuromodulation for aborting seizures [63]. It may also reduce the use of medical resources and anxiety around seizures.…”
Section: Seizure Prediction and Closed-loop Neurostimulationmentioning
confidence: 99%
“…However, pairing matched motor commands and somatosensory feedback following successful execution of intentional FES‐assisted movements may be more relevant in the context of neurorehabilitation 19 . The synchronization of descending activity from the motor cortex with the ascending sensory information may be responsible for enhancing the neuroplastic changes underlying functional improvements 20 . BCI technology promotes engagement of the central nervous system in a way that the executed FES‐assisted movements match the patient’s intention (ie, motor command).…”
Section: Introductionmentioning
confidence: 99%